PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP LOYALITAS PENUMPANG MELALUI KEPUASAN SEBAGAI VARIABEL INTERVENING (Studi pada penumpang Kereta Api Kaligung Relasi Semarang – Tegal) - Nugrahandini, Shinta Ayuni; Purbawati, Dinalestari (Jurnal Ilmu Administrasi Bisnis, 2019)
PT KAI is a company engaged in the field of public transport train services in Indonesia. The fierce competition in transportation services and the failure of Kaligung train to achieve targets of passenger in 2016, has made PT KAI strive to carry out various strategies to maintain its costumers. Companies are required to be able to provide good service balanced with price that are in accordance with what is given, so costumer will always use the services. This type of research used explanatory research with questionnaire as a method of collecting data. The sample in this study amounted to 100 passengers in the Kaligung train relation Semarang - Tegal using accidental sampling technique. The result showed that any effects positively and significant on service quality as well as price on passenger’s satisfaction and passenger’s loyalty, along with passenger’s satisfaction to passenger’s loyalty. Based on the sobel test, there was an effect between service quality toward passengger’s loyalty through passengger’s satisfaction with full-mediated. While for the effect between price toward passengger’s loyalty through passengger’s satisfaction, there was a partial-mediation. The suggestions for this research is to increase the service quality by coaching all of the employees who directly interact with passengers and provide security to control traffic for pasenggers’s ease in the station. So that, the pasengger would be satisfy and loyal to use Kaligung train